Trade Restrictiveness Indices in Presence of Externalities: An Application to Non-Tariff Measures - John Beghin; Anne-Célia Disdier; Stéphan Marette (Center for Economic Studies and ifo Institute (CESifo), 2014)
We extend the trade restrictiveness index approach to the case of market imperfections and domestic regulations addressing them. We focus on standard-like non-tariff measures (NTMs) affecting cost of production and potentially enhancing demand by reducing negative externalities. We apply the framework to the database of Kee et al. (2009) and derive ad valorem equivalents (AVEs) for NTMs. About 39% of the product lines affected by NTMs exhibit negative AVEs, indicating a trade-facilitating effect of these measures. Accounting for the trade-facilitating effect of NTMs significantly reduces previous measures of countries' trade policy restrictiveness obtained while constraining these NTMs to be trade reducing.
Keywords: F13; F18; Q56; 330; non-tariff measures; externalities; ad valorem equivalents; trade restrictiveness indices